Memahami Hakikat Islam dan Realitas Kaum Muslim: Upaya Membangun Masyarakat Madani - Luk Luk Nur Mufidah (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2016)
Islam puts man in a dimension not only of individuals, but also in the social dimension as a member of a community. It is important for us to be able to give a bright picture of the main components in shaping the society we desire. In fact, some people still displays paradoxical attitudes in the dissemination of the teachings and values ​​of Islam in social intercourse. For that, the basic concept of the Islamic community in fact laid on the principle of balance and harmony. Balance means a harmonious relationship between the vertical and horizontal dimensions, individual and social. global awareness of the resurrection of Islam who was covering the Muslim community today, by reviving the basic values ​​of religion, many believed to be a way out of any slump. Despite the steps limping and panting, the Muslims began to have a deep awareness to develop and memperkasakan themselves as religious people are civilized and progress.